IoT based security system and intelligent home automation multi monitoring and control systems - Mohammed H. Ali; Nisreen K. Ali (IAES International Journal of Robotics and Automation (IJRA), 2019)
This paper presents the execution of savvy Smart Home with frameworks and propelled advances. A Home Automation System uses the technology of IoT for the screening and controlling of the electrical and electronic appliances at home from any remote area by essentially utilizing a Smartphone. The key control framework utilizes a remote Bluetooth system and a remote IoT strategy that gives remote access to the advanced cells. The framework configuration does not expel the current electrical switches yet it gives a more secure control over it with the low voltage utilization method. This framework is intended to control electrical gadgets all through the house easily by introducing it, usability, savvy plan and actualize. There has been rising interest for a secure framework that must be tried, true and fast in reaction to the ventures and organization. Arduino makes the circuit and programming technology to design and operate wireless water monitoring system. The Water level in the tank is displayed on the Smartphone by the Water level app.